2014
DOI: 10.1007/s00449-014-1250-1
|View full text |Cite
|
Sign up to set email alerts
|

Toxic influence of silver and uranium salts on activated sludge of wastewater treatment plants and synthetic activated sludge associates modeled on its pure cultures

Abstract: Toxic impact of silver and uranium salts on activated sludge of wastewater treatment facilities has been studied. Some dominating cultures (an active nitrogen fixer Agrobacterium tumifaciens (A.t) and micromyces such as Fusarium nivale, Fusarium oxysporum, and Penicillium glabrum) have been isolated and identified as a result of selection of the activated sludge microorganisms being steadiest under stressful conditions. For these cultures, the lethal doses of silver amounted 1, 600, 50, and 300 µg/l and the le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Some of them mentioned that activated sludge growth is inhibited at Cr 6+ concentrations above 5 mg/L, while others report growth inhibition at concentrations above 25 mg/L. However, all researchers agree that Cr 6+ is definitely an activated sludge growth inhibitor at higher concentrations [4,19,24,35].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some of them mentioned that activated sludge growth is inhibited at Cr 6+ concentrations above 5 mg/L, while others report growth inhibition at concentrations above 25 mg/L. However, all researchers agree that Cr 6+ is definitely an activated sludge growth inhibitor at higher concentrations [4,19,24,35].…”
Section: Resultsmentioning
confidence: 99%
“…A few studies addressed the toxic influence of heavy metals on activated sludge of municipal wastewater treatment plants [4,19,[23][24][25]. Tyupa DV, et al [19] reported lethal doses of silver at 1, 50, 300, and 600 µg/L and lethal doses of uranium at 120, 1,500, and 1,000 mg/L, respectively, in activated sludge from a wastewater treatment plant. Liu G and Wang J [24] investigated the effect of nano-copper and nanomagnesium particles on activated sludge.…”
Section: Sci Forschenmentioning
confidence: 99%
See 1 more Smart Citation